Peer Influence Sebagai Mekanisme Organik Internalisasi Nilai Disiplin dalam Program Karakter Sekolah - Syifa Fauziah; Sapriya Sapriya; Intan Megasari (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2026)
This study examines the process of internalizing the values of responsibility and discipline through the One Day One Character (ODOC) Program at SMAN 2 Lembang. Using a qualitative approach with a case study design, data were collected through in-depth interviews with 16 informants, participant observation, and document analysis, and were then analyzed thematically using NVivo. The findings identified four phases of the internalization trajectory: external compliance, habituation, internalization of values, and autonomous disposition, which progress from extrinsic motivation toward autonomous self-regulation in accordance with Self-Determination Theory and Krathwohl’s affective taxonomy. The novelty of this research lies in the revelation of peer influence as an organic mechanism of internalization: the program’s structural design particularly communal transparency and public recognition through the Character Star indirectly triggers normative peer pressure that operates autonomously. Teachers serve as the initial catalyst; however, once group norms are established, horizontal dynamics among students take over the function of formal supervision. The implication is that effective character programs need to design conditions that strategically activate organic peer influence as a motor for sustainable internalization.